2010
DOI: 10.1186/1471-2229-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Rice stripe necrosis virus resistance locus and yield component QTLs using Oryza sativa × O. glaberrima introgression lines

Abstract: BackgroundDeveloping new population types based on interspecific introgressions has been suggested by several authors to facilitate the discovery of novel allelic sources for traits of agronomic importance. Chromosome segment substitution lines from interspecific crosses represent a powerful and useful genetic resource for QTL detection and breeding programs.ResultsWe built a set of 64 chromosome segment substitution lines carrying contiguous chromosomal segments of African rice Oryza glaberrima MG12 (acc. IRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 56 publications
2
59
0
Order By: Relevance
“…glaberrima (Brar, 2005). In collaboration with Institut de Recherche pour le Développement (IRD), France, Centro International de Agricultura Tropical (CIAT) based in Columbia has developed chromosome segment substitution lines (CSSLs) with O. glaberrima introgressions into O. sativa (Tohme, 2008), and a rice stripe necrosis virus resistance locus was identified using CSSLs from Caiapo (O. sativa, subgroup japonica)×MG 12 (O. glaberrima) (Gutiérrez et al, 2010). The CSSLs developed by CIAT and IRD have been used by collaborators for the localization of genes/QTLs for important traits such as drought resistance, panicle architecture, root development, iron toxicity resistance, bacterial leaf blight resistance and other agronomic traits (Tohme, 2008).…”
Section: Origin Of Oryza Glaberrima and Its Role In Rice Breedingmentioning
confidence: 99%
“…glaberrima (Brar, 2005). In collaboration with Institut de Recherche pour le Développement (IRD), France, Centro International de Agricultura Tropical (CIAT) based in Columbia has developed chromosome segment substitution lines (CSSLs) with O. glaberrima introgressions into O. sativa (Tohme, 2008), and a rice stripe necrosis virus resistance locus was identified using CSSLs from Caiapo (O. sativa, subgroup japonica)×MG 12 (O. glaberrima) (Gutiérrez et al, 2010). The CSSLs developed by CIAT and IRD have been used by collaborators for the localization of genes/QTLs for important traits such as drought resistance, panicle architecture, root development, iron toxicity resistance, bacterial leaf blight resistance and other agronomic traits (Tohme, 2008).…”
Section: Origin Of Oryza Glaberrima and Its Role In Rice Breedingmentioning
confidence: 99%
“…The whole donor genome is represented by a set of small, contiguous overlapping fragments. Such introgression lines (ILs) have been utilized in rice [112][113][114], tomato [115,116], soybean [117] and groundnut [118].…”
Section: Introgression Of Superior Alleles From Wild Speciesmentioning
confidence: 99%
“…In plants, segregation distortion has been encountered in maize (Mangelsdor and Jones 1926), rice (McCouch et al 1988), wheat (Zhang and Dvorák 1990;Faris et al 1998;Kumar et al 2007), barley (Graner et al 1991;Li et al 2010), tobacco (Cameron and Moav 1957), tomato (Paterson et al 1988), alfalfa (Echt et al 1994), and coffee (Ky et al 2000). Segregation distortion, also called "meiotic drive," may be caused by genetic elements, including gametic selection (pollen tube competition, lethal pollen, and preferential fertilization), zygotic selection, interspecific sterility genes (S), and chromosome translocation (Lyttle 1991;Kumar et al 2007;Gutiérrez et al 2010;Liu et al 2010). It has been suggested that meiotic drive elements are highly important for the evolution of recombination and sexual reproduction (Hurst and Werren 2001;Jaenike 2001;Li et al 2010).…”
Section: Rf 6 and The Linked Marker Loci Showed Segregation Distortionmentioning
confidence: 99%
“…Moreover, only one amphiploid was discovered to contain the Rf gene for CMS 514A after testing 59 different germplasm sources, including the maintainer of CMS 514A, which restores fertility to other CMS types (Wang et al 2007; this study). Taken together that CMS 514A has an H. tuberosus cytoplasm and the Rf 6 gene was from the wild species H. angustifolius, the segregation distortion may be caused by several factors, such as gametic selection, interspecific S gene, and chromosome translocation (Lyttle 1991;Kumar et al 2007;Gutiérrez et al 2010;Liu et al 2010).…”
Section: Rf 6 and The Linked Marker Loci Showed Segregation Distortionmentioning
confidence: 99%